Three moments of masculinizing politics in the colonial / capitalist power pattern - Assis Clímaco, Danilo (2018)
This article brings up the central features of the manly aspect revitalized by the pattern of capitalist / colonial power and outlines how the patriarchal modulation of the pattern of power occurs in three concrete examples: First: the consolidation of the patriarchy salary in Europe, between XIX and XX centuries. Second, the long process of hyper masculinization of black people in the US during the XX century, and, finally, the sudden process of indigenous hyper masculinization (and kaibilization) in Guatemala, between the 1970s and 1980s. From the joint vision of the three cases, markedly differentiated by the racial classification of the world population, of both, the general mode of action of the contemporary power pattern, and the historical specificities in which this occurs one gets an understanding of the masculinizing politics in the colonial / capitalist power pattern.